Identification of the na‛ar in the Ugaritic Texts - Cutler, B.
ersch. 1977; ṣuḫar(t)u in Mari and Alalakh, na‛ar, ne‛ārāh in Hebr. historical texts as in Ugarit designate high born persons in service of state or lord: ‘squire’, ‘knight’, not necessarily young.